2006
DOI: 10.1002/humu.20399
|View full text |Cite
|
Sign up to set email alerts
|

Long contiguous stretches of homozygosity in the human genome

Abstract: Single nucleotide polymorphisms (SNPs) are the most common sequence variation in the human genome; they have been successfully used in mapping disease genes and more recently in studying population genetics and cancer genetics. In a population-based association study using high-density oligonucleotide arrays for whole-genome SNP genotyping, we discovered that in the genomes of unrelated Han Chinese, 34 out of 515 (6.6%) individuals contained long contiguous stretches of homozygosity (LCSHs), ranging in the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 31 publications
8
112
1
Order By: Relevance
“…The longest track identified in the 55 URO individuals was 52.57 Mb, which is much greater than the 27.32 and 17.91 Mb previously described by Li et al 21 and Gibson et al, 22 respectively. These long tracts of homozygosity were frequently observed in our cohort and are due to RC resulting from consanguineous marriages going back more than three generations.…”
Section: Identified Rohmentioning
confidence: 50%
“…The longest track identified in the 55 URO individuals was 52.57 Mb, which is much greater than the 27.32 and 17.91 Mb previously described by Li et al 21 and Gibson et al, 22 respectively. These long tracts of homozygosity were frequently observed in our cohort and are due to RC resulting from consanguineous marriages going back more than three generations.…”
Section: Identified Rohmentioning
confidence: 50%
“…Research on ROHs has started to gain impetus, as evidenced by the increasing number of publications after the first study by Gibson et al 12 reported the abundance of ROHs in the human genome of outbred populations. Further studies have investigated the population characteristics of ROHs in healthy individuals, [13][14][15] and also performed association analyses to identify ROHs that are associated with complex diseases and traits in a case-control study design. [16][17][18] To circumvent the limitations of the previous study by Díaz de Ståhl et al, 10 we conducted a study in a Swedish population by genotyping 100 individuals using the Affymetrix SNP Array 6.0 (Affymetrix, Santa Clara, CA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…25 This assessment is somewhat contrasted by other studies that suggest that long homozygous segments are common in the human genome. [28][29][30] However, our results indicate that small homozygous segments around 1 Mb in length are quite common in both inbred and outbred individuals with genome-wide totals in excess of 40Mb per average individual (data not shown). This result agrees with previous estimates of total homozygosity based on the length of each segment.…”
Section: Discussionmentioning
confidence: 64%